2009
DOI: 10.1016/j.bbmt.2009.01.009
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Review of the Outcome after Second or Subsequent Allogeneic Transplantation

Abstract: The failure of allogeneic stem cell transplant (allo-SCT) is cumbersome. We analyzed our experience in a second allo-SCT. Between the years 1981 and 2007, 144 patients underwent 2 or more allo-SCT. The first to second transplant interval ranged from 18 days to 13.25 years (median 98 days). The most frequent indications for the second SCT were activity of the basic disease (78), rejection (37), and engraftment failure (25). Twenty-nine of the 144 (20%) patients transplanted survived more then a year with treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
25
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 23 publications
7
25
3
Order By: Relevance
“…The observed 1-year NRM of 36% among our patients was similar to the reported rates (23-45%) for HSCT2 using the same donor 8,26,29 and at the low end of the range of NRM (35-51%) described for HSCT2 involving donor change. 8,26,28,37 With a CR rate of 75% on day +30, early disease control was satisfying.…”
Section: Gi Tractsupporting
confidence: 73%
See 3 more Smart Citations
“…The observed 1-year NRM of 36% among our patients was similar to the reported rates (23-45%) for HSCT2 using the same donor 8,26,29 and at the low end of the range of NRM (35-51%) described for HSCT2 involving donor change. 8,26,28,37 With a CR rate of 75% on day +30, early disease control was satisfying.…”
Section: Gi Tractsupporting
confidence: 73%
“…12,13 Furthermore, 85% of our patients achieved engraftment, comparable to a 67-97% engraftment rate observed after second HSCT from HLA-matched related or unrelated donors. 10,25,26,28,29 Additionally, sustained full donor chimerism could be established in all patients with continuing CR, as observed by other studies on HSCT2. 10,26 Considering our patients' high disease burden, intensive pretreatment and the frequently short median interval after HSCT1, the overall toxicity was moderate.…”
Section: Treatmentsupporting
confidence: 51%
See 2 more Smart Citations
“…The role of the conditioning regimen in allo-HCT2 outcomes is difficult to determine as the majority of the survival effect is thought to relate to GVL; however, recent studies have demonstrated that reduced-intensity conditioning (RIC) has improved outcomes compared with myeloablative conditioning (MAC) owing to a reduction in toxicity. 5,6 No series has reported the outcomes in patients conditioned purely with fludarabinemelphalan (Flu-Mel), which is presently the commonest RIC regimen used in Australasia. 7 Here, we report a series of patients receiving allo-HCT2 using Flu-Mel conditioning.…”
mentioning
confidence: 99%